Antenas de microfita sobre substrato de ferrita de níquel dopadas com zinco - Castro, Kaíck Viana de Oliveira (2018)
Microstrip antennas have a potential that was only initially studied in 1953, to receive more attention only in the 1970s. Since then, several techniques, methods of analysis, algorithms, and materials have been developed to study, understand and produce these antennas. Advantages such as low cost, small dimensions, low weight and volume, aerodynamically advantageous format, possibility to have flat or curved format made this antenna one of the most interesting for the military area, and now for commercial and industrial area. This work has as objective at the development of substrates for microfite antennas using Ni-Zn-type Ferrites using the Sol-Gel technique, a physicochemical process that allows the obtaining of nanometric particles, in view of the ease of execution of this technique. The experiments consisted in the production of three types of ferrites, NiFe2O4, ZnFe2O4 and Ni0,5Zn0,5Fe2O4 in which these pellets were used as substrates of the microfite antennas. Then, simulations were carried out using commercial HFSS software to verify the influence of the magnetic properties of the material on antenna parameters such as return loss, bandwidth, and Smith's chart. The simulated results were divided into groups called dielectric and standard, in which these groups differed in the presence or absence of the magnetic characteristics of the material. All the results were compared with the values measured and analyzed by verifying some effects such as the reduction of the resonance frequency of the antennas